1993
DOI: 10.1021/bi00055a024
|View full text |Cite
|
Sign up to set email alerts
|

Probing the combining site of an anti-carbohydrate antibody by saturation-mutagenesis: Role of the heavy-chain CDR3 residues

Abstract: The carbohydrate-binding site in Fab fragments of an antibody specific for Salmonella serogroup B O-polysaccharide has been probed by site-directed mutagenesis using an Escherichia coli expression system. Of the six hypervariable loops, the CDR3 of the heavy chain was selected for exhaustive study because of its significant contribution to binding-site topography. A total of 90 mutants were produced and screened by an affinity electrophoresis/Western blotting method. Those of particular interest were further c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
58
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 27 publications
11
58
0
Order By: Relevance
“…Enthalpy-Entropy Compensation-Enthalpy-entropy compensation plots have been observed previously during carbohydrate binding to lectins (25,26) and antibodies (21,27,28) and are attributed to the unique properties of water (26). A change in binding enthalpy is always compensated by the change of binding entropy.…”
Section: Relative Contributions Of Enthalpy and Entropy To The Bindinmentioning
confidence: 59%
“…Enthalpy-Entropy Compensation-Enthalpy-entropy compensation plots have been observed previously during carbohydrate binding to lectins (25,26) and antibodies (21,27,28) and are attributed to the unique properties of water (26). A change in binding enthalpy is always compensated by the change of binding entropy.…”
Section: Relative Contributions Of Enthalpy and Entropy To The Bindinmentioning
confidence: 59%
“…c Data also presented in Table II. residues with all 19 other amino acids, and none of the mutants showed any improvement in oligosaccharide binding (1). Phage-display techniques were then used to modify additional CDR residues, and modest improvements were found for some CDR H2 mutants (30,33).…”
Section: Discussionmentioning
confidence: 99%
“…One means of exploring this question is to attempt to generate mutant anti-carbohydrate antibodies with higher affinities, either by design of site-directed mutants or by randomizing selected codons in a phage library. However, the production of antibodies with improved affinities that maintain antigen specificity has proven challenging (1)(2)(3)(4). For example, in an exhaustive site-directed mutagenesis study of CDR 1 H3 of an anti-Salmonella Fab, Brummell et al (1) found that all of the 90 mutant Fabs produced showed similar or decreased binding affinity for the O-antigen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well recognized that mutations at the CDRs or FWR structurally adjacent to the CDRs can modulate and optimize the antigen-binding interface (4)(5)(6)(7), and several studies have used saturated mutagenesis of CDR position to explore the effect of various mutations on affinity and specificity (8)(9)(10)(11).…”
mentioning
confidence: 99%